Tectono-metamorphic evolution of the Wadi Hafafit Culmination (central Eastern Desert, Egypt). Implication for Neoproterozoic core complex exhumation in NE Africa - H. ABD EL-NABYY; W. FRISCH; W. SIEBEL (Geologica Acta, 2009)
The Neoproterozoic rock assemblages in the Wadi Hafafit Culmination (WHC) can be subdivided into two main units which are separated by the Nugrus Thrust. The structurally higher Nugrus unit is mainly composed of low grade micaschists, metavolcanic, serpentinites, and metagabbros. The overthrusted Hafafit unit forms the Hafafit domes and is composed of ortho- and para-gneisses associated with amphibolite and ultramafic rocks. Mineral chemistry and thermobarometry indicate that the WHC was affected by two main metamorphic phases. The first metamorphic phase (M1), observed in the micaschists of the Nugrus unit, is characterized by greenschist- facies conditions. Garnet-biotite and garnet-muscovite geothermometry, as well as temperatures calculated by means of the TWEEQU program yield temperatures of 400°–550°C, whereas the white mica geobarometer reveals pressure of 3.7-4.9 kbar for this metamorphic phase (M1). The second metamorphic phase (M2), observed in gneisses and amphibolites of the Hafafit unit, is characterized by amphibolite-facies conditions. Garnet-biotite, garnet-amphibole and amphibole-plagioclase geothermometry yield temperatures of 600°–750°C, whereas the garnet-hornblende-plagioclase-quartz geobarometer indicates pressures of 6-8 kbar for the second metamorphic phase (M2). Sm-Nd and Rb-Sr whole rock-mineral isochron ages around 590 Ma for gneisses and amphibolites probably represent cooling from the metamorphic thermal peak which was attained around 600 Ma or slightly earlier. A 3-stage geologic evolution model is proposed for the tectonic evolution of the WHC. The first stage started earlier than 680 Ma ago with rifting and ocean floor spreading at a time which is as yet unspecified. It was followed by a second stage of subduction and emplacement of subduction-related granitoids around 620-640 Ma. At this time, the Hafafit region has become an active margin with the production of large amounts of calc-alkaline subduction-related volcanic and plutonic sequences. Subduction was terminated by collision and NW-ward Nugrus Nappe thrusting under greenschist-facies conditions (M1) around 620-640 Ma. At this stage, rocks of Hafafit unit were subjected to intense deformation and metamorphism in amphibolite facies (M2). Next came the third stage of late-orogenic extension and crustal thinning that was controlled by the Najd transform faults (620-580 my) and that resulted in exhumation of the Hafafit domes through a combination of transpression and lateral extrusion.